2014
DOI: 10.11607/ijp.3674
|View full text |Cite
|
Sign up to set email alerts
|

Denture Adhesives Improve Mastication in Denture Wearers

Abstract: This assignment applies to all translations of the Work as well as to preliminary display/posting of the abstract of the accepted article in electronic form before publication. If any changes in authorship (order, deletions, or additions) occur after the manuscript is submitted, agreement by all authors for such changes must be on file with the Publisher. An author's name may be removed only at his/her written request. (Note: Material prepared by employees of the US government in the course of their official d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 24 publications
2
33
0
2
Order By: Relevance
“…One of the main goal of prosthetic treatment is to restore masticatory function in conventional denture wearers who suffer from decreased oral proprioception, alterations in chewing dynamics that occur with prosthetic devices and reduced denture stability and retention which is further compounded by physiologic bone resorption of the denturebearing ridge (17) . Again, the responses of the patients towards the tested adhesives were favouring their use as it improved their ability to chew and this is in accordance with multiple studies and surveys (9,10,17) . This may be attributed to the fact that improved retention and stability results in an increase in the force that can be applied during chewing, leading to fewer strokes.…”
Section: Discussionmentioning
confidence: 99%
“…One of the main goal of prosthetic treatment is to restore masticatory function in conventional denture wearers who suffer from decreased oral proprioception, alterations in chewing dynamics that occur with prosthetic devices and reduced denture stability and retention which is further compounded by physiologic bone resorption of the denturebearing ridge (17) . Again, the responses of the patients towards the tested adhesives were favouring their use as it improved their ability to chew and this is in accordance with multiple studies and surveys (9,10,17) . This may be attributed to the fact that improved retention and stability results in an increase in the force that can be applied during chewing, leading to fewer strokes.…”
Section: Discussionmentioning
confidence: 99%
“…When hydrated with moisture or saliva, denture adhesives swell, filling the spaces between the denture and oral mucosa and providing strong cohesive bonds between the two (Kumar et al, ). This can result in improved denture retention and stability, which in turn improves chewing efficacy and ability, increases comfort and wearer satisfaction, and minimizes the accumulation and ingress of food particles between the denture and oral mucosa (Goncalves, Viu, Goncalves, & Garcia, ; Grasso, ; Kapur, ; Kumar et al, ; Munoz et al, ; Papadiochou, Emmanouil, & Papadiochos, ; Tarbet, Boone, & Schmidt, ).…”
Section: Introductionmentioning
confidence: 99%
“…When hydrated with moisture or saliva, denture adhesives swell, filling the spaces between the denture and oral mucosa and providing strong cohesive bonds between the two (Kumar et al, 2015). This can result in improved denture retention and stability, which in turn improves chewing efficacy and ability, increases comfort and wearer satisfaction, and minimizes the accumulation and ingress of food particles between the denture and oral mucosa (Goncalves, Viu, Goncalves, & Garcia, 2014;Grasso, 2004;Kapur, 1967;Kumar et al, 2015;Munoz et al, 2012;Papadiochou, Emmanouil, & Papadiochos, 2015;Tarbet, Boone, & Schmidt, 1980). Several studies have cited food entrapment or accumulation under dentures as one of the most common complaints in denture wearers, leading to pain and discomfort (Aghdaee, Rostamkhani, & Ahmadi, 2007;Brunello & Mandikos, 1998;Gosavi, Ghanchi, Malik, & Sanyal, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the application of DA to either well-or ill-fitting dentures leads to improvement in denture retention and wearer satisfaction [11][12][13] . Furthermore, a shortening of masticating cycle time and increases in occlusal force and masticating rate have been observed with DA application [14][15][16] . It has also been found that DA influence the retentive force of dentures worn by patients with xerostomia 17,18) .…”
Section: Introductionmentioning
confidence: 99%